2016
DOI: 10.1177/1359105315572452
|View full text |Cite
|
Sign up to set email alerts
|

Men, rheumatoid arthritis, psychosocial impact and self-management: A narrative review

Abstract: Rheumatoid arthritis (RA) is a chronic disease affecting fewer men than women. We systematically reviewed the literature on impact and self-management of RA men. Twenty eight papers were included, and grouped into two categories: Psychosocial impact of RA;and Coping and self-management. This review finds gender differences relating to quality of life; work; distress; self-management; coping; and support. We conclude there is a dearth of literature focussing on RA men only, and mixed gender studies include insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 64 publications
4
31
0
Order By: Relevance
“…RA affects more women than men (approximately 30% of all patients are men) 3 and may take a different course in women compared to men, with male sex being a potential predictor of remission in RA 4. A recent literature review 5 found that the majority of gender‐based research on the psychosocial impact and self‐management in rheumatology either addressed the differences between men and women, reflecting the preponderance of women with the condition, or focused solely on women. Very little research has focused solely on men, and there is no consensus on whether gender affects a person's ability to cope with RA.…”
Section: Introductionmentioning
confidence: 99%
“…RA affects more women than men (approximately 30% of all patients are men) 3 and may take a different course in women compared to men, with male sex being a potential predictor of remission in RA 4. A recent literature review 5 found that the majority of gender‐based research on the psychosocial impact and self‐management in rheumatology either addressed the differences between men and women, reflecting the preponderance of women with the condition, or focused solely on women. Very little research has focused solely on men, and there is no consensus on whether gender affects a person's ability to cope with RA.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the survey were presented and the importance of equity issues in RCT was discussed. Discussion was further stimulated by the presentation of a narrative review of psychosocial effects of RA on men 28 . This review demonstrated potential differences between subgroups of a population and how, in this case, sex may influence the choice of outcome or patient responses.…”
Section: Resultsmentioning
confidence: 99%
“…This review demonstrated potential differences between subgroups of a population and how, in this case, sex may influence the choice of outcome or patient responses. The review found that men and women experience different types of effect on their quality of life 28 . Specifically, women reported lower quality of life on items relating to emotional state than men, whereas men reported lower quality of life on items relating to social activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although RA affects more women than men 2 , men tend to be under-represented in PA trials in RA 44,48 . Also, men with RA may require different support strategies than women 49 . As a result, recruitment of predominantly women to a PA intervention may not simply be indicative of gender differences in prevalence rates of RA, but may also reflect different coping styles and management preferences.…”
Section: Discussionmentioning
confidence: 99%